Trends in corporate financial strategies: Analyzing investment efficiency among listed Indonesian companies - Adinda Febiyanti; Lintang Venusita (Akuntansi dan Teknologi Informasi, 2024)
The main objective of this study is to investigate the impact of conservatism, debt maturity, and debt covenants on investment efficiency in Indonesian firms, with a focus on the food and staples retail and food and beverage sub-sectors. This study aims to address information asymmetry between agents and principals, using agency theory as the theoretical framework. A quantitative approach is used using secondary data sourced from financial reports available on the IDX website and company websites. This study took a sample of 329 companies using non-probability sampling technique. Data processing using linear regression method. The results show that conservatism significantly improves investment efficiency, while debt maturity and debt covenants do not show a significant effect. This study underscores the importance of conservative financial reporting practices in improving investment efficiency in the Indonesian corporate sector.